Efek Teratogenik Ekstrak Etanol Daun Sirsak (Annona muricata L) Terhadap Fetus Tikus Putih Galur Wistar - Erjon Erjon; Jouliyano Dwiputri; Sari Meisyayati (Jurnal Penelitian Sains, 2019)
Ethanolic extract of leaves of “sirsak” (Annona muricata L) has been proven to be effective in convulsant, inflammatory, hiperuresemia, hyperglycemia and hypertension to patients. The aim of this study was to evaluated teratogenicity effect of ethanolic extract of leaves of sirsak (Annona muricata L) leaves in Wistar rats. Ethanolic extract of leaves of “sirsak” were administered orally at dose level of 98 mg/kgbw, 196 mg/kg bw , 392 mg/kgbw on day eighth to eighteenth of gestation. At day 20th of gestation, laparoctomy was performed to retrieve the fetuses. Evaluation was done towards the fetus skeletal, organ and fetal weight. The at all doses did not cause any fetus resorption, did not cause malformation in organ and skeleton but cause fetus growth failure. Ethanolic extract of leaves of sirsak at doses of 98, 196, and 392 mg/kgbw in rats did not have the teratogenic effect.